MACROECONOMIC FACTORS OF INCREASING THE RANKING IN THE GLOBAL INNOVATION INDEX - Numanov Kamolitdin Farhadovich (American Journals, 2023)
The article examines the macroeconomic factors for improving the rating in the Global Innovation Index (GII), in particular, based on the analysis of the methodological framework, groups data sources and macroeconomic indicators of the GII, and identifies quantitative indicators of the index.
Keywords: Global Innovation Index, rating, cost sub-index, results sub-index, indicators, indicators, ratio, macroeconomics.